Additional Financing for Transport and Information and Communication Technology - Independent Evaluation Group (World Bank, Washington, DC, 2015)
In May 2005, the Bank adopted a new policy and new procedures on Additional Financing (OP/BP13.20) for investment lending, replacing the previous policy on supplemental financing. This policywas later revised in March 2012. This learning product assesses the performance of the AdditionalFinancing (AF) operations approved since then and draws lessons from their implementationexperience. The assessment focuses on AF in projects of the Transport and Information andCommunication Technology (ICT) Global Practice (GP). This was selected as the first batch ofoperations to review because they represent a large share in lending volume, as well as the fact that there is an existing AF study conducted by the former Transport Anchor which this review coulduse to verify the AF portfolio. This note aims to enhance the understanding of the way it has been used and how it has affected the project outcomes, through reviewing a subset of the AF portfolio for which the relevant data was readily available. The review notes the limitation of the small sample. More areas could be investigated when the data of more projects become available.